2016
DOI: 10.1186/s13063-016-1520-0
|View full text |Cite|
|
Sign up to set email alerts
|

Thromboprophylaxis using combined intermittent pneumatic compression and pharmacologic prophylaxis versus pharmacologic prophylaxis alone in critically ill patients: study protocol for a randomized controlled trial

Abstract: BackgroundVenous thromboembolism (VTE) remains a common problem in critically ill patients. Pharmacologic prophylaxis is currently the standard of care based on high-level evidence from randomized controlled trials. However, limited evidence exists regarding the effectiveness of intermittent pneumatic compression (IPC) devices. The Pneumatic compREssion for preventing VENous Thromboembolism (PREVENT trial) aims to determine whether the adjunct use of IPC with pharmacologic prophylaxis compared to pharmacologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Combined pharmacologic prophylaxis and mechanical prophylaxis with intermittent pneumatic compression (IPC) and/or graduated compression stockings (GCS) is a potential option in critically ill patients with sepsis and septic shock. No high-quality studies of this approach in septic patients, or even critically ill patients in general, exist; however, further research is ongoing [523]. A Cochrane review [524] of 11 studies in surgical patients suggested that combined prophylaxis was more effective than either modality used alone.…”
mentioning
confidence: 99%
“…Combined pharmacologic prophylaxis and mechanical prophylaxis with intermittent pneumatic compression (IPC) and/or graduated compression stockings (GCS) is a potential option in critically ill patients with sepsis and septic shock. No high-quality studies of this approach in septic patients, or even critically ill patients in general, exist; however, further research is ongoing [523]. A Cochrane review [524] of 11 studies in surgical patients suggested that combined prophylaxis was more effective than either modality used alone.…”
mentioning
confidence: 99%
“…The trial protocol and statistical analysis plan have been published previously. [ 9 , 10 ] The trial is registered at Clinicaltrials.gov: NCT02040103 and Current controlled trials: ISRCTN44653506. The PREVENT trial is being conducted in 19 sites in Saudi Arabia, Canada, Australia, and India.…”
Section: Methodsmentioning
confidence: 99%
“…1 ). Exclusion criteria have been detailed in the protocol manuscript [ 5 ]. To enhance the generalizability of our findings, we permit the use of a broad array of IPC devices from various manufacturers intended for DVT prophylaxis.…”
Section: Methodsmentioning
confidence: 99%
“…These outcomes test the secondary hypotheses that IPC reduces the extent of incident proximal lower-extremity DVT and reduces central-venous-catheter- and non-central-venous-catheter-related incident proximal lower-extremity DVT Unilateral incident proximal lower-extremity DVT Bilateral incident proximal lower-extremity DVT Number of veins with DVT. As per our protocol, the venous system is examined by documenting compressibility at the following six sites: common femoral, proximal superficial femoral, mid superficial femoral, distal superficial femoral, popliteal veins and trifurcation [ 5 ]. We will document the number of veins involved as a measure of DVT extent Complete occlusion (with one vein at least non-compressible) Incomplete occlusion (with all veins at least partially compressible) Central-venous-catheter-related incident proximal lower-extremity DVT as defined previously [ 5 ] Non-central-venous-catheter-related incident proximal lower-extremity DVT Secondary outcomes related to lower-extremity DVT other than incident proximal lower-extremity DVT Prevalent – proximal DVT.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation